Developing an Integrated Information System for Performance Management in Indonesian Higher Education - Badjuka, Alexander H.; Mozin, Sri Yulianty; Nani, Yacob Noho (Universitas Muhammadiyah Yogyakarta, 2026)
Indonesian higher education institutions continue to face significant challenges in implementing the Government Agency Performance Accountability System (SAKIP), primarily due to fragmented information systems and manual reporting practices. At Gorontalo State University (UNG), these inefficiencies undermine accountability, delay decision-making, and compromise data accuracy. This qualitative descriptive case study explores how digital integration can address these institutional challenges. The findings revealed that a lack of system interoperability across planning, financial, and performance units leads to data redundancy, inconsistent reporting, and high administrative workloads. A simulation of the e-SAKIP workflow demonstrated a 65% reduction in reporting time and a 40% decrease in data duplication, underscoring its operational impact. In response, this study introduces a prototype of a centralized, cloud-based platform, e-SAKIP, that integrates planning, budgeting, monitoring, and reporting functions into a single digital ecosystem. The novelty of this study lies in developing the first API-based integrated governance model for Indonesian public universities, addressing the critical gap between siloed legacy systems and national SAKIP compliance requirements. Theoretically, the research contributes to digital governance literature by operationalizing Good University Governance (GUG) and New Public Management (NPM) principles through technological integration. Practically, the proposed e-SAKIP model offers a scalable solution for other universities facing similar challenges and provides actionable policy insights to strengthen institutional accountability, data reliability, and digital readiness across Indonesia’s higher education sector.